Hereditary Hemorrhagic Telangiectasia and Myocardial Infarction - Martínez-Quintana, Efrén; Rodríguez-González, Fayna; Gopar-Gopar, Silvia (International Journal of Angiology, 2016)
Hereditary hemorrhagic telangiectasia, also known as Osler–Weber–Rendu syndrome, is an autosomal dominant genetic disorder that leads to epistaxis, gastrointestinal bleeding, iron deficiency anemia, and arteriovenous malformations at the lungs, the liver, and the brain. However, due to its rarity and its unspecific findings on routine examinations, diagnosis is not easy unless suspected due to hypoxemia or paradoxical embolism. We present a case of a 46-year-old-woman with hereditary hemorrhagic telangiectasia and hypoxemia who presented a myocardial infarction secondary to paradoxical embolism through pulmonary arteriovenous malformations.
Keywords: hereditary hemorrhagic telangiectasia; Osler–Weber–Rendu syndrome; pulmonary arteriovenous malformations; myocardial infarction